Dissent in dangerous times - Sarat, Austin (Ann Arbor : University of Michigan Press, 2005)
While dissent has played a central role in our national history and in the American cultural imagination, it is usually dangerous to those who practice it, and always unpalatable to its targets. War does not encourage the tolerance of opposition at home any more than it does on the front: if the War on Terror is to be a permanent war, then the consequences for American political freedoms cannot be overestimated. The contributors examine the role of political opposition in our times, the nature of political repression in liberal societies, the political and legal implications of fear, and how past generations responded to similar situations. From publisher description.
Terrorism, dissent & repression : an introduction / Austin Sarat -- Political idealization & its discontents / Wendy Brown -- The epistemology of state emotion / Lauren Berlant -- The weakest link? : academic dissent in the "War on terrorism" / Hugh Gusterson -- The new McCarthyism : repeating history in the War on terrorism / David Cole -- Constitutional reason of state : the fear factor / Nancy L. Rosenblum.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: USA -- Government; USA -- Regierung; United States -- Politics and government -- 2001-2009.; Radicalism -- United States; Freedom of expression -- United States; Protest movements -- United States; Political culture -- United States; Political psychology; Radicalisme -- États-Unis.; Liberté d'expression -- États-Unis.; Contestation -- États-Unis.; Culture politique -- États-Unis.; Psychologie politique; États-Unis -- Politique et gouvernement -- 2001-; États-Unis -- Politique et gouvernement -- 2001-2009.; SOCIAL SCIENCE -- General; SOCIAL SCIENCE -- Sociology -- General; Freedom of expression; Political culture; Political psychology; Politics and government; Protest movements; Radicalism; United States; Politische Kultur; Protestbewegung; Radikalismus; United States -- Politics and government -- 2001-2009.; Radicalism -- United States; Freedom of expression -- United States; Protest movements -- United States; Political culture -- United States; Political psychology; 2001-2009; Dissent; Loyalty; Electronic books